Continuous spinal anaesthesia: A retrospective analysis of 318 cases - Beh, Zhi Yuen; Yong, Phui Sze Au; Lye, Siyu; Eapen, Sneha Elizabeth; Yoong, Chee Seng; Woon, Kwee Lian; Lim, Jimmy Guan Cheng (Medknow Publications, 2018)
Background and Aims: Continuous spinal anaesthesia (CSA) is an underutilised anaesthetic technique. Our objectives were to evaluate the use of CSA in our institution, its efficacy, ease to use and safety. Methods: This was a retrospective analysis conducted in a tertiary centre. Records of all patients who underwent surgery and received CSA between December 2008 and July 2017 were reviewed. Their demographic profiles, type and duration of surgery were analysed. The outcomes measured were the success of CSA, technical evaluation and difficulties encountered, intraoperative haemodynamics, usage of vasopressors and any reported complications. Statistical analysis was done using Chi-square test. Results: Three hundred and eighteen patients (94%) successfully underwent surgery using CSA. Twenty cases (6%) had failed CSA, of which five of them had CSA insertion failure, while the rest failed to complete the operation under CSA, thus requiring conversion to general anaesthesia. Patients who have had an initial intrathecal local anaesthetic (LA) volume ≥1.5 ml had higher odds (odds ratio (OR) 2.78; 95% confidence interval [CI], 1.70–4.57) of developing hypotension compared to those who had <1.5 ml (P < 0.001). There were no reported post-dural puncture headache, neurological sequelae or infection. Conclusion: CSA is a useful anaesthetic technique with low failure rate. The key to achieving haemodynamic stability is by giving a small initial bolus, then titrating the block up to required height using aliquots of 0.5 ml of intrathecal LA through the catheter.